Pemahaman Tentang Konsep Tubuh Orang Percaya Sebagai Bait Roh Kudus Berdasarkan I Korintus 6:12-20 - Lengkong, Ester (Sekolah Tinggi Teologi Injili Indonesia Palu, 2024)
A deep understanding of the concept of the body of believers as the temple of the Holy Spirit is crucial in the context of Christian spirituality. This article examines phenomena involving behaviors detrimental to the body among Christian believers, such as alcohol consumption, smoking, homosexuality, prostitution, lesbianism, and pornography. Based on the analysis of 1 Corinthians 6:12-20, this study highlights the importance of comprehending the significance of the body of believers within the framework of God's truth. A lack of understanding of this concept can lead to behaviors deviating from religious teachings. The practical implications of a deeper understanding of the body as the temple of the Holy Spirit are also discussed in this article.